2018
DOI: 10.18778/1429-3730.50.04
|View full text |Cite
|
Sign up to set email alerts
|

Relation between work efficiency and labor cost in Poland

Abstract: The basic goal of this document is to research the changes in work efficiency level, as well as labor costs and evaluation of their relation in Poland in comparison to other EU countries. Research period embraced the years 2000–2016. Desired research objective was achieved with the use of review of the literature method, deduction, description and simple statistical and visualization technics (Eurostat, GUS). The analysis of changes and proportions between unit labor costs and labor productivity is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Many authors mentioned low labour productivity in Poland. Kapela (2018), analysing the years 2000-2016, demonstrated that labour productivity in Poland was one of the lowest among member states. In turn, Mrówczyńska-Kamińska (2012) argues that in Poland very low labour productivity affects both agriculture and the whole agri-food sector.…”
mentioning
confidence: 99%
“…Many authors mentioned low labour productivity in Poland. Kapela (2018), analysing the years 2000-2016, demonstrated that labour productivity in Poland was one of the lowest among member states. In turn, Mrówczyńska-Kamińska (2012) argues that in Poland very low labour productivity affects both agriculture and the whole agri-food sector.…”
mentioning
confidence: 99%